Kultur der Selbstachtung - Grom, Bernhard (Horyzonty Wychowania, 2017)
In the past three decades psychology has been showing the significance of a positive sense of one’s own value for life satisfaction among children, youth and adults and has worked out methods helpful in becoming aware and realizing one’s own needs and rights. The aim is not to support egocentric or narcissistic attitudes, but to prevent a feeling of dejection and lack of happiness. What is the meaning of such cultivation of the sense of one’s own value? According to Kant’s mind ethics, man is obliged to provide himself with „moral recognition” and to guard his dignity. Theological ethics and spirituality supplement this one-sidedly moral justification of cultivating respect for yourself and shows that man should respect himself in his whole as „likeness” of the Creator and His „friend”, loved by the Son of God „to the uttermost”, for whom He laid down His life (John 13, 1; 15, 13-15). Together with this God he should love himself and avoid any self-depreciation. Christian spirituality may make this message more effective if it listens to what psychology says about the threats to the sense of one’s own value.